Fetal Magnetic Resonance in the Diagnosis of CNS Malformations: Experience of the Coimbra Pediatric Hospital - Liberal, Maria João (2021)
Fetal ultrasound (US) is the most commonly used prenatal exam to evaluate fetal growth, however, in some cases the results are inconclusive or insufficient, in these situations fetal magnetic resonance imaging (MRI) becomes a diagnostic supplement of extreme significance.The aim of this work is to evaluate the role of fetal MRI in the diagnosis of central nervous system (CNS) malformations in the Central Pediatric Hospital of Coimbra from May 2012 to May 2019.The sample consisted of 85 pregnant women who performed a fetal MRI to evaluate the CNS of the fetus during this time, at the imaging department of the central hospital of Portugal, making a total of 91 examinations. The image process of each one of the expectant mothers was analyzed and relevant data such as the age of the pregnant, weeks of gestation, fetal US findings, MRI findings, fetal artifacts, twin pregnancy, the neuroradiologist responsible for the examination report and the US verification by the MRI scan of CNS lesions were collected.It was verified that the majority of patients was between 30 and 40 years and highest number of CNS fetal MRI scans were performed before 24 weeks and at 30 and 33 weeks of gestation. The most observed occurrences on MRI refer ventriculomegaly, midline malformations, posterior fossa anomalies and subarachnoid space alterations. It was possible to determine that the verification of the suspicion of the US by MRI is not related to the age group or the weeks of gestation.